Configurational paths of organizational and technological innovation to firm performance using fuzzy-set QCA analysis (Latin-American Journal of Computing, 2021)
The relationship between organizational and technological innovation and its effect on firm performance have received attention for the literature with divided perspectives. Both modes of innovation are considered as important sources of competitive advantage. Empirical evidence so far indicates two directions regarding the relationship between organizational and technological innovation: those supporting that organizational innovation enables technological innovation, and those with the opposite perspective. Recent evidence suggests a holistic approach to understand the intrinsic relationship between the firm’s innovative activities. This study uses the dynamic capabilities view of the firm and implements a fuzzy-set qualitative comparative analysis (fsQCA) for a sample of enterprises in Latin America, to clarify complex causal interactions of the firm’s attributes and different forms of innovation leading to high performance. The results show several equifinal solutions leading to business success. Additionally, the results identify three different archetypes of firms based on innovative behavior.